Identification of male sterility maintenance, fertility restoration responses, and combining ability in sunflower (Helianthus annuus L.): MALE STERILITY MAINTENANCE, FERTILITY RESPONSES, AND COMBINING ABILITY IN SUNFLOWER - C THEJASWAN; S D NEHRU; H P MEENA; SUNILKUMAR SURESH GANIGER; SUBHASHCHANDRA L SHABANNAVAR (Journal of Oilseeds Research, 2026)
A study was conducted to examine the sterility maintenance and fertility restoration behaviour of 11 backcross derived inbred lines across seven CMS lines, as well as to identify the hybrids surpassing the best checks in Line × Tester mating design during the rabi season of 2023. The resulting 56 fertile hybrids out of the 77 hybrids that were produced, together with four check hybrids (KBSH-44, KBSH-78, KBSH-85, and GK 2002), were evaluated in alpha lattice design and parents were evaluated in RCBD design with two replications during summer, 2024 for seed yield and related traits. Eight backcross derived inbred lines (PB-1620, PB-1638, PB-1639, PB-1640, PB-1641, PB-1648, PB-1649, PB-1649-1) were identified as fertility restorers for all seven CMS lines. Two lines (PB-1643-1 and PB-1647) were sterility maintainers, and one line (PB-1650) was a partial restorer for all seven CMS lines. CMS 207B and CMS 903B were identified as good general combiners for earliness, seed yield plant-1 and oil content, whereas tester PB-1640 was a good general combiner for seed yield plant-1 and oil content, and PB-1649-1 was a good general combiner for earliness and seed yield plant-1. Hybrids with higher SCA have also shown higher magnitude of heterosis over all the checks, notably NDCMS 2A × PB1640, CMS 903A × PB1639, and CMS 234A × PB1649-1 for earliness, seed yield/plant and oil content, making them promising hybrid genotypes for multilocation trials to confirm commercial potential. Backcross-derived inbred lines that maintained complete sterility across all seven CMS lines could serve as promising new CMS sources in future breeding programs.